ANALYSIS OF REWETTING TIME AND TEMPERATURE DISTRIBUTIONS DURING COOLING PROCESS IN VERTICAL RECTANGULAR NARROW CHANNEL - Catrawedarma, Bagus; -, Indarto; Juarsa, Mulya; Antariksawan, Anhar Riza (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2013)
Cooling process to analyze effect of gap size to rewetting time and temperature distributions were studied from transient temperature of surface plate. It as result of experiment using two vertical plate with the initial temperature about 600Â°C. Debit and temperature of cooling water are 0,09 L/s and saturated temperature. The gap sizes were changed from 1 mm, 2 mm, and 3 mm. As the results showed that the smaller the gap size, the longer the rewetting time. Pattern of temperature distribution is similar at initial condition for all of gap sizes and the smaller the gap sizes, the longer the time of decreasing temperature.